반응형
derivative_br_41

41. ddx(x)sqrt(4x2)\frac{d}{dx} (x)sqrt(4-x^2)

ddxx4x2=4x2+x2x24x2=42x24x2 \begin{aligned} &\frac{d}{dx} x\sqrt{4-x^2}=\sqrt{4-x^2}+x\frac{-2x}{2\sqrt{4-x^2}}\\ &=\frac{4-2x^2}{\sqrt{4-x^2}} \end{aligned}


42. ddxsqrt(x21)/x\frac{d}{dx}sqrt(x^2-1)/x

ddxx21x=2x22x21x21x2=1x21x21x2=1x2x21 \begin{aligned} &\frac{d}{dx} \frac {\sqrt{x^2-1}} x =\frac {\frac{2x^2}{2\sqrt{x^2-1}}-\sqrt{x^2-1}}{x^2}\\ &=\frac{1}{\sqrt{x^2-1}}-\frac{\sqrt{x^2-1}}{x^2} \\ &=\frac{1}{x^2\sqrt{x^2-1}} \end{aligned}


43. ddxx/sqrt(x21)\frac{d}{dx}x/sqrt(x^2-1)

ddxxx21=x21x2x2x21x21=1x21x2x21(x21)=1x21(x21) \begin{aligned} &\frac{d}{dx} \frac x {\sqrt{x^2-1}}\\ &=\frac{\sqrt{x^2-1}-x\frac{2x}{2\sqrt{x^2-1}}}{x^2-1}\\ &=\frac{1}{\sqrt{x^2-1}}-\frac{x^2}{\sqrt{x^2-1}(x^2-1)}\\ &=-\frac{1}{\sqrt{x^2-1}(x^2-1)} \end{aligned}


44. ddxcos(arcsinx)\frac{d}{dx} cos(arcsinx)

ddxcos(arcsinx)=sin(arcsinx)11x2=x1x2 \begin{aligned} &\frac{d}{dx} cos(arcsinx)\\ &=-sin(arcsinx)\frac{1}{\sqrt{1-x^2}}\\ &=-\frac{x}{\sqrt{1-x^2}} \end{aligned}


45. ddxln(x2+3x+5)\frac{d}{dx} ln(x^2 + 3x + 5)

ddxln(x2+3x+5)=2x+3x2+3x+5 \begin{aligned} &\frac{d}{dx} ln(x^2 + 3x + 5)\\ &=\frac{2x+3}{x^2 + 3x + 5} \end{aligned}


46. ddx(arctan(4x))2\frac{d}{dx}(arctan(4x))^2

ddx(arctan(4x))2=2arctan(4x)41+16x2=8tan14x1+16x2 \begin{aligned} &\frac{d}{dx}(arctan(4x))^2\\ &=2arctan(4x)\frac{4}{1+16x^2}\\ &=\frac{8\tan^{-1}{4x}}{1+16x^2} \end{aligned}


47. ddxcubert(x2)\frac{d}{dx}cubert(x^2)

ddxx23=ddxx23=23x13=23x3 \begin{aligned} &\frac{d}{dx}\sqrt[3]{x^2}=\frac{d}{dx}x^{\frac{2}{3}}\\ &=\frac{2}{3}x^{-\frac{1}{3}}=\frac{2}{3\sqrt[3]{x}} \end{aligned}


48. ddxsin(sqrt(x)lnx)\frac{d}{dx}sin(sqrt(x) lnx)

ddxsin(xlnx)=cos(xlnx)(12xlnx+x1x)=cos(xlnx)ln(x)x+2x2x \begin{aligned} &\frac{d}{dx}sin(\sqrt{x} lnx)\\ &=cos(\sqrt{x} lnx)(\frac{1}{2\sqrt x}lnx+\sqrt x \frac{1}{x})\\ &=cos(\sqrt{x} lnx)\frac{ln(x)\sqrt{x}+2\sqrt x}{2x} \end{aligned}


49. ddxcsc(x2)\frac{d}{dx}csc(x^2)

ddxcsc(x2)=csc(x2)cot(x2)2x=2xcsc(x2)cot(x2)cf)ddxcsc2x=2cscx(cscxcotx)=2csc2xcotx \begin{aligned} &\frac{d}{dx}csc(x^2)=-csc(x^2)cot(x^2)2x\\ &=-2xcsc(x^2)cot(x^2)\\ &cf) \frac{d}{dx}csc^2x=2cscx(-cscxcotx)\\ &=-2csc^2xcotx\\ \end{aligned}


50. ddx(x21)/lnx\frac{d}{dx}(x^2-1)/lnx

ddxx21lnx=2xlnx((x21)1x)(lnx)2=2xlnxx+(1/x)(lnx)2 \begin{aligned} &\frac{d}{dx}\frac{x^2-1}{lnx}=\frac{2xlnx-((x^2-1)\frac{1}{x})}{(lnx)^2}\\ &=\frac{2xlnx-x+(1/x)}{(lnx)^2} \end{aligned}



Author: crazyj7@gmail.com

'Math' 카테고리의 다른 글

derivatie100 [51-60]  (0) 2019.11.18
D operator  (0) 2019.11.07
derivative100 [31-40]  (0) 2019.11.05
derivative100 [21-30]  (0) 2019.11.04
derivative100 [11-20]  (0) 2019.10.31

+ Recent posts